The dark side of the sublime Distinguishing a threat-based variant of awe. - Gordon, Amie M.; Stellar, Jennifer E.
Theoretical conceptualizations of awe suggest this emotion can be more positive or negative depending on specific appraisal processes. However, the emergent scientific study of awe rarely emphasizes its negative side, classifying it instead as a positive emotion. In the present research we tested whether there is a more negative variant of awe that arises in response to vast, complex stimuli that are threatening (e.g., tornadoes, terrorist attack, wrathful god). We discovered people do experience this type of awe with regularity (Studies 1 & 4) and that it differs from other variants of awe in terms of its underlying appraisals, subjective experience, physiological correlates, and consequences for well-being. Specifically, threat-based awe experiences were appraised as lower in self-control and certainty and higher in situational control than other awe experiences, and were characterized by greater feelings of fear (Studies 2a & 2b). Threat-based awe was associated with physiological indicators of increased sympathetic autonomic arousal, whereas positive awe was associated with indicators of increased parasympathetic arousal (Study 3). Positive awe experiences in daily life (Study 4) and in the lab (Study 5) led to greater momentary well-being (compared with no awe experience), whereas threat-based awe experiences did not. This effect was partially mediated by increased feelings of powerlessness during threat-based awe experiences. Together, these findings highlight a darker side of awe.